Smart guide for the blind: System analysis and design of a mobile application for real-time object detection and navigation support - Wazirali, Raniyah; Alkhamash, Eman; Gordon, Lucia Carrion (Edelweiss Applied Science and Technology, 2025)
This paper presents the development, system analysis, and design of the Smart Guide for the Blind (SGB), a mobile application created to support visually impaired individuals in navigating their surroundings safely and independently. The system leverages the smartphone’s camera alongside real-time object detection models, including TensorFlow and YOLOv5, to identify surrounding obstacles and communicate them through auditory cues and vibration alerts. Designed as a cost-effective and portable assistive tool, SGB targets users who may not have access to expensive specialized technologies. Comprehensive testing demonstrated the application’s effectiveness in recognizing a wide range of common environmental objects, confirming its potential to enhance situational awareness and reduce navigation risks. By improving mobility, confidence, and day-to-day autonomy, the SGB contributes to broader societal goals of inclusion and accessibility. The project aligns with the Kingdom of Saudi Arabia’s Vision 2030 initiatives, which emphasize empowering individuals with disabilities and expanding the availability of innovative, technology-driven solutions to support their full participation in society.